Proceedings: Human Leukocyte Antigen Haplo‐Homozygous Induced Pluripotent Stem Cell Haplobank Modeled After the California Population: Evaluating Matching in a Multiethnic and Admixed Population. (13th March 2015) - Pappas, Derek James; Gourraud, Pierre-Antoine; Le Gall, Caroline; Laurent, Julie; Trounson, Alan; DeWitt, Natalie; Talib, Sohel
Summary: The development of a California‐based induced pluripotent stem cell (iPSC) bank based on human leukocyte antigen (HLA) haplotype matching represents a significant challenge and a valuable opportunity for the advancement of regenerative medicine. However, previously published models of iPSC banks have neither addressed the admixed nature of populations like that of California nor evaluated the benefit to the population as a whole. We developed a new model for evaluating an iPSC haplobank based on demographic and immunogenetic characteristics reflecting California. The model evaluates haplolines or cell lines from donors homozygous for a single HLA‐A, HLA‐B, HLA‐DRB1 haplotype. We generated estimates of the percentage of the population matched under various combinations of haplolines derived from six ancestries (black/African American, American Indian, Asian/Pacific Islander, Hispanic, and white/not Hispanic) and data available from the U.S. Census Bureau, the California Institute for Regenerative Medicine, and the National Marrow Donor Program. The model included both cis (haplotype‐level) and trans (genotype‐level) matching between a modeled iPSC haplobank and the recipient population following resampling simulations. We showed that serving a majority (>50%) of a simulated California population through cis matching would require the creation, redundant storage, and maintenance of almost 207 different haplolines representing the top 60 most frequent haplotypes from each ancestry group. Allowances for trans matching reduced the haplobank to fewer than 141 haplolines found among the top 40 most frequent haplotypes. Finally, we showed that a model optimized, custom haplobank was able to serve a majority of the California population with fewer than 80 haplolines. Abstract : This study developed a new model for evaluating an induced pluripotent stem cell (iPSC) haplobank based on demographic and immunogenetic characteristics reflecting California. Creation of a haplobank of iPSC lines homozygous for a variety of human leukocyte antigen (HLA) types, representative of different geographic populations and ethnic groups, could simplify HLA matching and provide matches for reasonable percentages of target populations and extend iPSC‐derived therapies beyond the autologous setting.